2013
DOI: 10.1371/journal.pone.0068582
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Infections in Adults with Atopic Disease and IgE Antibodies to Common Aeroallergens

Abstract: BackgroundAtopic diseases, including allergic rhinitis, allergic dermatitis and asthma, are common diseases with a prevalence of 30–40% worldwide and are thus of great global public health importance. Allergic inflammation may influence the immunity against infections, so atopic individuals could be susceptible to respiratory infections. No previous population-based study has addressed the relation between atopy and respiratory infections in adulthood. We assessed the relation between atopic disease, specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 22 publications
2
39
0
5
Order By: Relevance
“…Neither atopic dermatitis nor hay fever were associated with increased risk of any infection, pneumonia or any non‐respiratory tract infection, so we cannot confirm the association between dermatitis and increased risk of lower respiratory tract infections reported in a cross‐sectional study of 1008 individuals . Another case–control study with 174 cases found that atopic dermatitis was associated with increased risk of serious pneumococcal disease, defined as pneumococcal pneumonia, pneumococcal sepsis or other invasive pneumococcal infections .…”
Section: Discussionmentioning
confidence: 70%
“…Neither atopic dermatitis nor hay fever were associated with increased risk of any infection, pneumonia or any non‐respiratory tract infection, so we cannot confirm the association between dermatitis and increased risk of lower respiratory tract infections reported in a cross‐sectional study of 1008 individuals . Another case–control study with 174 cases found that atopic dermatitis was associated with increased risk of serious pneumococcal disease, defined as pneumococcal pneumonia, pneumococcal sepsis or other invasive pneumococcal infections .…”
Section: Discussionmentioning
confidence: 70%
“…Rantala et al. found that that adult atopics had more respiratory infections than non‐atopics and the number of respiratory infections increased with increasing levels of specific IgE antibodies to common allergens. However, another study by Rantala et al.…”
Section: Discussionmentioning
confidence: 99%
“…Atopic diseases have been reaching epidemic proportions worldwide over the recent years [1, 2]. The key factor driving this rising trend is increased exposure to aeroallergens.…”
Section: Introductionmentioning
confidence: 99%